The Ototoxicity of Chloroquine and Hydroxychloroquine: A Systematic Review - Fernandes,Carolina Pereira (2022)
Abstract Introduction Chloroquine and hydroxychloroquine are antimalarial drugs widely used in the treatment of rheumatic diseases. With the global pandemic caused by the new coronavirus, there was an increase in the prescription of these drugs, which led to a major concern regarding their ototoxic effects. Objectives The objective of the present study was to assess existing scientific evidence about the toxic effects of chloroquine and hydroxychloroquine on the peripheral and/or central auditory system. Data Synthesis A systematic literature review was performed by searching the PubMed (Medline), Scopus, Web of Science, LILACS, and SciELO electronic databases, in a search of articles that fullfiled the predefined inclusion and exclusion criteria. The review was conducted in three phases and, in all of them, analyses were performed by two independent researchers. Disagreements were discussed with a third researcher until a consensus was reached. A total of 437 articles were found and 8 were included in this review. Seven of the included studies reported hearing loss in their samples and presented a diagnostic hypothesis of ototoxicity induced by chloroquine or hydroxychloroquine. The most common type of hearing loss was sensorineural, with varying laterality and degrees of severity. The most frequently used audiological test was pure tone audiometry, and only two studies assessed brainstem evoked responses. Conclusion The scientific evidence compiled in this research showed that chloroquine and hydroxychloroquine have an ototoxic effect in the peripheral auditory system. These drugs can cause cochlear damage, including changes in the stria vascularis and lesions in sensory hair cells.